Comparação in vitro de diferentes materiais usados em retrobturações - Perez, Walter Blaya (2010)
This research intended to evaluate three different materials, in vitro, for their capacity of sealing in root-end fillings. The sample was consisted by 30 single root teeth, having primarily realized root canal treatment and subsequently resected three mm from the apex, in an angle of 90° in relation to its long axis and in its apex, cavities with ultrasonic tips were prepared. Subsequently they were retro filled with different materials, randomized divided in three groups of ten teeth each, according to the retrofilling product. Group 1: mineral trioxide aggregate (gray MTA Angelus®); Group 2: mineral trioxide aggregate (MTA Endo Sealer CPM®) and Group 3: a phosphate tricalcium cement. Its evaluation in relation to the apical sealing was obtained through the microleakage test with the Rodamine B solution 0.2%. Subsequently, the teeth were sectioned in their long axis by taking one of the parts and evaluating it in a dentistry microscope. Their images were captured and analyzed in the Image Tool 2.0 Software to determine the microleakage zones. The data was statistically analyzed using the STATA 9.0 program. First, an exploratory analysis of the data was realized referring to the studied variables. The dependent variable considered in this study was the percentage of stained dentin, regardless of the type of sealant used in each resected root. The differences between the values of microleakage in each material were statistically evaluated by the Kruskal-Wallis test considering a minimum level of sufficiency up to 5%. Before the analysis, the Schapiro-Wilk test was applied to verify the normality of the data distribution. According to the test, a pattern of non-normal distribution of the dependent variable (p=0.002) could be observed. Higher values of infiltration could be observed in the group that used a tricalcium phosphate cement in relation to groups that used mineral trioxide aggregate (gray MTA- Angelus®) and mineral trioxide aggregate (MTA Endo Sealer CPM®) (p<0.001). There was no significant difference in the values of infiltration between the MTA